Efektivitas Media Pembelajaran Berbasis Film Animasi Dr. Stone Terhadap Hasil Belajar Materi Induksi Elektromagnetik Pada Siswa Kelas XII SMAN 1 Jeneponto - Halimah, Andi; Permana, Imam; Ashar, Rachmat (Al-Khazini: Jurnal Pendidikan Fisika, 2022)
This study aims to determine the learning outcomes of students in SMAN 1 Jeneponto class on electromagnetic induction material not using the animated film Dr. Stone, to find out the learning outcomes of class XII students of SMAN 1 Jeneponto on electromagnetic induction materials using Dr. animated film as learning media. Stone, to find out the difference in the learning outcomes of class XII students of SMAN 1 Jeneponto on electromagnetic induction material, not using and using Dr. animation media. Stone, and to find out the animated film-based learning media, Dr. Stone is effective on the learning outcomes of class XII students of SMAN 1 Jeneponto on electromagnetic induction material. The type of research used is quasi-experimental. The research design used is the Noneequivalent control group design. The population in this study were students of class XII MIPA SMAN 1 Jeneponto. Sampling Research using Simple Random Sampling. The research sample used was 25 people in the experimental class and 25 people in the control class. The results showed that: 1) the learning outcomes of students in SMAN 1 Jeneponto class on electromagnetic induction material did not use the animated film Dr. Stone is mostly in the category of good learning outcomes with an average value of 59.4. 2) the learning outcomes of class XII students of SMAN 1 Jeneponto on electromagnetic induction materials using Dr. animated film as learning media. Stone is mostly in the category of good learning outcomes with an average score of 79.8. 3) Based on the results of data analysis, it was found that there were differences in the learning outcomes of students who were not taught using Dr.Stone’s animated film and those who were taught using Dr.Stone’s animated film. 4) Learning media based on Dr. animation film. Stone is effective on student learning outcomes seen from the average N-Gain score in the experimental class of 0.72 which is included in the high category, while the average N-Gain score in the control class is 0.46 which is included in the medium category. . The implications of this study are: 1) the results of this study indicate that the implementation of physics learning using Dr.Stone’s animated film-based learning media is effective on student learning outcomes so that it can be applied to further teaching activities. 2) For further researchers, the results of this study can be used as material for comparison, reference and challenges, especially those who want to conduct similar research so that students are more interested in participating in the learning process.